Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
OCLC: 1233305994
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Décoloniser l’imaginaire esthétique : Vers une écriture de nouveaux paradigmes caribéens - Kirchner-Blanchard, Catherine; Lefrançois, Frédéric (Revue d'Études Décoloniales, 2018)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

L’art périphérique montre l’afro-diaspora en environnement digital - del Rei, Mariana (revue Periferias, 2021)
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Pour un féminisme afro-latino-américain - Gonzalez, Leila (Revue d'Études Décoloniales, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Charla | Estética afro Identidad, saberes y resistencia - Banrepcultural (2019)
En esta charla conversaremos sobre las luchas históricas por la reivindicación de los derechos del pueblo afro que están detrás de su estética, específicamente en dos de sus expresiones femeninas: el turbante afro y el pelo natural, los cuales han servido como elementos de resistencia para la pervivencia de las prácticas y costumbres ancestrales. Como parte de la exposición temporal del Museo del Oro 'A bordo de un navío esclavista, La Marie-Séraphique' (que se presentó en Bogotá del 7 de octubre de 2018 al 7 de abril de 2019) hablamos en el museo sobre algunos peinados ancestrales, como la espina de pescado, las tropas, el hundidito, el ciempiés y la vicha, y sobre los usos, significados y modelos de los turbantes afro, como la cadena del esclavo, la autoridad, el kitambala, el enkeycha y el doek. El termino mata ‘e pelo surge de las expresiones propias de nuestras ancestras, que se referían al pelo afro cómo una gran mata (árbol), frondosa, incontrolable y rizada, que requería unos cuidados particulares por su condición crespa, abundante y diversa. El cuerpo de la mujer negra, raizal y palenquera ha estado históricamente ligado a las luchas por la reivindicación de los derechos del pueblo afro, siendo la mata ‘e pelo el elemento estético que más las ha transmitido. Entre las personas de ancestros africanos, la estética del pelo afro se remonta a un pasado cargado de lucha y resistencia, pues las trenzas fueron usadas para la elaboración de mapas que marcaban el camino a la libertad de los cimarrones. Las mujeres se reunían en el patio para peinar a las más pequeñas. Diseñaban en su cabeza un mapa lleno de caminitos y salidas de escape, en el que ubicaban los montes, ríos y árboles más altos. Así, al verlas, los hombres sabían cuáles rutas tomar. Su código, desconocido para los amos, les permitía a los esclavizados huir. El balance humano de la trata de cautivos africanos a través del Atlántico es dramático: con una inmensa brutalidad, desplazó a 13 millones de hombres, mujeres y niños entre la segunda mitad del siglo XVI y finales del siglo XIX. #ElMuseoDelOroTambiénEsAfro Producción Banco de la República Realización Santiago Martínez
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Presencia negra en Bogotá: Décadas 1940-1950-1960
La exposición Presencia negra en Bogotá hace parte de la investigación en Migraciones que desde la Universidad Nacional lideran Mercedes Angola y Maguemati Wabgou. Está presente en el Claustro de San Agustín, como un homenaje a los hacedores de grandes historias que se desconocen, personas cuyos aportes a la construcción de la sociedad colombiana y a la consolidación de la identidad nacional desde diversas perspectivas y disciplinas ha invisibilizado la historia colombiana. En compañía de sus protagonistas, acompáñenos en la formulación de nuevas preguntas de investigación en torno al aporte de la gente negra a Colombia y a países vecinos, pues no solo se ha producido migración interna sino, "fuga" hacia otros países. Invitados : Mercedes Angola, artista plástica e investigadora y Maguemati Wabgou, sociólogo e investigador.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

The Decolonial Turn in Media Studies in Africa and the Global South - Moyo, Last (Palgrave Macmillan, 2020)
This book develops a nuanced decolonial critique that calls for the decolonization of media and communication studies in Africa and the Global South. Last Moyo argues that the academic project in African Media Studies and other non-Western regions continues to be shaped by Western modernity’s histories of imperialism, colonialism, and the ideologies of Eurocentrism and neoliberalism. While Africa and the Global South dismantled the physical empire of colonialism after independence, the metaphysical empire of epistemic and academic colonialism is still intact and entrenched in the postcolonial university’s academic programmes like media and communication studies. To address these problems, Moyo argues for the development of a Southern theory that is not only premised on the decolonization imperative, but also informed by the cultures, geographies, and histories of the Global South. The author recasts media studies within a radical cultural and epistemic turn that locates future projects of theory building within a decolonial multiculturalism that is informed by trans-cultural and trans- epistemic dialogue between Southern and Northern epistemologies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; _Nettoyé

Por uma pedagogia crioula : memória, identidade e resistência no quilombo de Conceição das Crioulas – PE - Nascimento, Márcia Jucilene do (Universidade de Brasília, 2017)
This dissertation aims to describe the specific schooling process developed in the quilombo of Conceição das Crioulas, in Salgueiro / PE. This process was a result of the socio-historical reconstruction movement of the quilombo’s history, which started in the 1980s. This process triggered several conflicts, and priority was given to the regaining of their territory and to the search for educational practices with decolonizing ideals. Based on the individual and collective memories of Conceição das Crioulas people, we have registered the historical accounts of the community’s resistance to the domination and oppression systems imposed to them since the arrival of the creole founders until today. The methodological trajectory was based on interviews, informal conversations and the analysis of a video-documentary, specifically recorded for this research. This path also allowed us to evaluate how we have perceived and done our school education over a period of twenty-two years, whose milestone is the inauguration, in 1995, of Professor José Mendes school, a local public school where grades 6th to 9th are taught. First, this paper addresses important elements for the beginning of this search. Next, it describes practices and specific actions of the education of Conceição das Crioulas. After that, it draws a comparative analysis about this and other pedagogical experiences, highlighting connections and significant distances between them. Finally, at the end of the last chapter, it conceptualizes this experience, which was named Crioula Pedagogy in the community.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; _À analyser